Vigorous Physical Activity Is Associated With Better Glycated Hemoglobin and Lower Fear of Hypoglycemia Scores in Youth With Type 1 Diabetes: A 2-Year Follow-Up Study - Jabbour, Georges (Frontiers in Physiology, 2020)
To correlate glycated hemoglobin (HbA1c) and fear of hypoglycemia scores with physical activity (PA) levels in children and adolescents with type 1 diabetes over a period of 2 years. Twenty-eight children and 33 adolescents with type 1 diabetes have been assessed for their PA profile. Personal and medical data for the patients were collected at baseline (visit 0: V0), one year (V1) and two years later (V2). At baseline, children with type 1 diabetes engaged in less moderate to vigorous PA (MVPA) (p<0.01) per week than adolescents. These results did not differ across visits. At the contrary, adolescent spent fewer time in vigorous physical activity (VPA) (p<0.01) than children did (p<0.01). Fear of hypoglycemia scores correlated significantly with VPA levels (β=-0.41; p=0.03, β=-0.44; p=0.06 and β=-0.61; p=0.001). For HbA1c (%) significant correlations were reported with VPA levels (β=-0.54; p=0.02, β=-0.47; p=0.03, β=-0.62; p=0.01) across visits. Body mass index percentile correlated with total screen time (β=0.28; p=0.02, β=0.29; p=0.01 and β=0.31; p=0.04) and overall PA levels (β=-0.52; p=0.02, β=-0.42; p=0.03, β=-0.42; p=0.01) Performing more vigorous PA a week is associated with better HbA1c with lower perceived fear of hypoglycemia among youth with type 1 diabetes. Therefore dedicating more time in VPA may be an appropriate advice for patients with type 1 diabetes.